Virulence potential of biofilm producing Staphylococcus pseudintermedius, Staphylococcus aureus and Staphylococcus coagulans causing skin infections in companion animals - Andrade, Mariana (2022)
Coagulase-positive staphylococci (CoPS) account for most bacteria-related pyoderma in companion animals. Emergence of methicillin-resistant strains of Staphylococcus pseudintermedius (MRSP), Staphylococcus aureus (MRSA) or Staphylococcus coagulans (MRSC), often with multidrug-resistant (MDR) phenotypes, is a public health concern. The study collection comprised 237 staphylococci (S. pseudintermedius (n = 155), S. aureus (n = 55) and S. coagulans (n = 27)) collected from companion animals, previously characterized regarding resistance patterns and clonal lineages. Biofilm production was detected for 51.0% (79/155), 94.6% (52/55) and 88.9% (24/27) of the S. pseudintermedius, S. aureus and S. coagulans, respectively, and was a frequent trait of the predominant S. pseudintermedius and S. aureus clonal lineages. The production of biofilm varied with NaCl supplementation of the growth media. All S. pseudintermedius and S. aureus strains carried icaADB. Kaplan–Meier survival analysis of Galleria mellonella infected with different CoPS revealed a higher virulence potential of S. aureus when compared with other CoPS. Our study highlights a high frequency of biofilm production by prevalent antimicrobial-resistant clonal lineages of CoPS associated with animal pyoderma, potentially related with a higher virulence potential and persistent or recurrent infections.